2011
DOI: 10.1038/icb.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

CD137 differentially regulates innate and adaptive immunity against Mycobacterium tuberculosis

Abstract: Protective immunity against Mycobacterium tuberculosis is primarily mediated by the interaction of antigen-specific T cells and antigen presenting cells, which often depends on the interplay of cytokines produced by these cells. Costimulatory signals represent a complex network of receptor–ligand interactions that qualitatively and quantitatively influence immune responses. Thus, here we investigated the function of CD137 and CD137L, molecules known to have a central role in immune regulation, during human tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
(107 reference statements)
2
15
0
Order By: Relevance
“…Recent literature has suggested the engagement of the CD137 signaling pathway during M. tuberculosis infection in humans and mice (Fernández Do Porto et al 2011;Palma et al 2010). Our data support these earlier findings and provide insights into the mechanisms by which the CD137-CD137L system contributes to the immune resistance against M. tuberculosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent literature has suggested the engagement of the CD137 signaling pathway during M. tuberculosis infection in humans and mice (Fernández Do Porto et al 2011;Palma et al 2010). Our data support these earlier findings and provide insights into the mechanisms by which the CD137-CD137L system contributes to the immune resistance against M. tuberculosis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the strikingly low levels of TNF-␣ measured in the BALF from M. tuberculosis-infected CD137L −/− mice may contribute to the greater bacterial burden and granuloma-like lesions. It has been shown that CD137L is required for sustained TNF production in macrophages (Kang et al 2007), and that blockade of CD137 leads to reduced TNF production by T cells from TB patients (Fernández Do Porto et al 2011). Interestingly, CD137L has recently been shown to associate with TNF receptor 1, and to utilize TNF receptor 1 for its signal transduction .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A function for 4-1BB at earlier thymic differentiation stages has not been reported; however, some studies have shown that 4-1BB can regulate TNF-a expression (46,47) and vice versa (48), suggesting a possible link between the two. Overexpression of TNF-a under control of its natural promoter has been reported to block early thymocyte development at the DN1 to DN2 stage, promoting accelerated thymic atrophy (49) and mirroring our own observations in the NOD thymus.…”
Section: Discussionmentioning
confidence: 98%
“…A total of 2 3 10 5 monocytes were plated in round-bottom 96-well plates at differing ratios to iNKT cells as described in Results. 4-1BB blocking Ab (4B4-1; BD, Bergen County, NJ) and 4-1BB ligand blocking Ab (C65-485; BD) (30) were added at the beginning of the coculture at 5 mg/ml each. When indicated in text, CD1d blocking Ab (CD1d42; BD Pharmingen, Oxford, U.K.) was added at 10 or 25 mg/ml.…”
Section: Inkt-monocyte Coculture Assaysmentioning
confidence: 99%